2018
DOI: 10.3390/min8100441
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Magmatic Water Content and Oxidation State for Porphyry-Style Au Mineralization: An Example from the Giant Beiya Au Deposit, SW China

Abstract: The Beiya Au deposit is the largest Cenozoic Au deposit in the Jinshajiang-Ailaoshan porphyry metallogenic belt. Numerous studies document that high water content and fO2 are vital factors for the generation of Au mineralization. In this belt, only the Wandongshan and Hongnitang districts are considered to be of economic importance, while the other districts, such as Bailiancun, are barren. So in order to reveal the importance of water content and oxidation state for Beiya porphyry-style Au mineralization, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…),Bao et al (2018),Huang et al (2019),Sepidbar et al (2019),Zhou et al (2019),Yang et al (2020), andZheng et al (2020) [Colour figure can be viewed at wileyonlinelibrary.com]…”
mentioning
confidence: 99%
“…),Bao et al (2018),Huang et al (2019),Sepidbar et al (2019),Zhou et al (2019),Yang et al (2020), andZheng et al (2020) [Colour figure can be viewed at wileyonlinelibrary.com]…”
mentioning
confidence: 99%
“…(c) Bao et al. (2018) suggested the magma source of the Beiya deposit is located at about 8 km depth.…”
Section: Discussionmentioning
confidence: 99%
“…(b) It was concluded that metal-rich fluids of large-scale porphyry ore deposits should be supplied from deep (≧6 km) mafic magma chambers (Hou et al, 2020). (c) Bao et al (2018) suggested the magma source of the Beiya deposit is located at about 8 km depth. Moreover, the study area is characterized with anomalously high heat flow values (55-103 mW/m 2 ) that are only less than the highest heat flow values in Yunnan, China (80-120 mW/m 2 , located in the Tengchong volcanic area; Jiang et al, 2018).…”
Section: Upper Crustal Anomaliesmentioning
confidence: 99%
“…In the present case, the temperature range shown is in the range of 828–688°C with an average of 755°C, making it a better candidate for mineralization evident in the Kuthori‐Bagori association (Majumdar & Gogoi, 2020). Higher oxidation increases the SO 2 /H 2 S of the fluid and enhances the ability of ore fluid to scavenge and transport copper (Bao et al, 2018; Wyborn, 2002).…”
Section: Discussionmentioning
confidence: 99%